RELASI KUASA DAN HIERARKI SOSIAL DI PESANTREN: FENOMENA FEODALISME DAN GUS-GUSAN - Jati Pamungkas (Universitas Teuku Umar, 2026)
This study examines power relations, social hierarchies, and symbolic dynamics within Indonesian pesantren environments, focusing on two central issues: cultural feudalistic practices and the phenomenon of “gus-gusan.” Through a literature review of works published between 2010 and 2025, the research analyzes how the authority of the kiai is constructed through the accumulation of symbolic, social, and cultural capital, as well as how hierarchical structures within pesantren are maintained through adab (ethics) and traditions of ta‘zīm (reverence). Drawing on Max Weber’s theory of charisma and the framework of Symbolic Interactionism, this paper highlights that kiai authority is rooted not only in scholarly competence but also in cultural perceptions of charisma, genealogical lineage, and inherited spiritual legitimacy.The study finds that feudalistic tendencies in pesantren do not manifest as political feudalism but rather as patrimonial patterns arising from hereditary leadership, symbolic control, and absolute obedience within the santri community. Meanwhile, the phenomenon of “gus-gusan” the attribution of the honorary title Gus without genealogical or scholarly basis emerges as a consequence of modernization, social media, and the commodification of religious symbols. The shifting meaning of the title “Gus” indicates a transformation in the structure of religious legitimacy in the digital age.The findings underscore the importance of repositioning values of adab, scholarship, and accountability so that pesantren can preserve their moral authority while adapting to the demands of modernity. This study contributes to theoretical understanding of the transformation of religious authority and the dynamics of power within traditional Islamic institutions in the Indonesian archipelago.